2005
DOI: 10.1016/j.jtbi.2004.10.025
|View full text |Cite
|
Sign up to set email alerts
|

The self-organization of speech sounds

Abstract: The speech code is a vehicle of language: it defines a set of forms used by a community to carry information. Such a code is necessary to support the linguistic interactions that allow humans to communicate. How then may a speech code be formed prior to the existence of linguistic interactions? Moreover, the human speech code is discrete and compositional, shared by all the individuals of a community but different across communities, and phoneme inventories are characterized by statistical regularities. How ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 22 publications
3
106
0
1
Order By: Relevance
“…Ultimately, all these design features will require such explanation, and a similar research effort aimed at understanding the evolution of duality of patterning (in both biological and cultural terms) is underway (see, e.g. Oudeyer 2005;Zuidema & de Boer in press). In §4, we will turn to the issue of interactions between biological and cultural evolutionary accounts.…”
Section: Language Designmentioning
confidence: 99%
“…Ultimately, all these design features will require such explanation, and a similar research effort aimed at understanding the evolution of duality of patterning (in both biological and cultural terms) is underway (see, e.g. Oudeyer 2005;Zuidema & de Boer in press). In §4, we will turn to the issue of interactions between biological and cultural evolutionary accounts.…”
Section: Language Designmentioning
confidence: 99%
“…On the other hand, it has been shown that those same universal trends reflect constraints of human embodiment (both of the articulatory system and the auditory system) as well as optimality constraints on sound recognition and sound reproduction [27]. Moreover recent simulations carried out in my group [12], [34] have shown that agents with similar embodiment constraints as human beings are able to autonomously self-organise vowel systems if they recruit a bi-directional associative memory to associate sound patterns with articulatory gestures. Even more interest-ingly, the emergent vowel systems have the same statistical distribution as observed in human languages (see figure 1 from [12]).…”
Section: Methodsmentioning
confidence: 94%
“…An example of a scaffold is the space of possible phonemes: in none of the experiments in this book, agents had to learn the distinctive sounds of their language. These "scaffolded" features may be brought in at a later stage or form the subject of other experiments, such as work on the emergence of vowel systems (de Boer 2000;Oudeyer 2005).…”
Section: The Do's and Don'ts Of Artificial Language Evolutionmentioning
confidence: 99%
“…The above account of the history of the research on language as a complex adaptive system did not refer to the experiments on the emergence of vowel systems and phonology (de Boer 2000;Oudeyer 2005). I also left out the work performed on event recognition, but I will come back to this in Chapter 3.…”
Section: Other Research Avenuesmentioning
confidence: 99%